REGENERATION OF SPENT TRANSFORMER OIL (Journal of Engineering, 2024)
The regeneration of spent transformer oil taken from Al-Dora power station was studied. The regeneration process includes settling, filtration, thermo vacuum evaporation, and clay treatment. The settling was done by gravity to remove the mechanical particles. The filtration was done by filter paper [whatman quality! and 18.5 cm diameter). Thermo vacuum evaporation at 175°C and 241 mm Hg was used for removing the dissolved water and light petroleum impurities. The clay treatment was used for final improvement of transformer oil properties. Iraqi clay. Algerian clay and zeolite (A) were used and the results were compared. It was studied the effect of clay to oil ratio and the mixing time on the water content, break down voltage and the acidity. It was considered that the best operation conditions are clay to oil ratio 2/100, and time 5 min. In these conditions the oil has water content 32 ppm, break down voltage 55 kV and acidity 0.028 mg KOH/g oil. It was found that Algerian clay gives better improvement than zeolite and Iraqi elay using the same operating conditions. Langmuir. Freundlich, and the combination of them adsorption isotherms were studied in this investigation and it was found that Freundlich adsorption isotherm well represented the adsorption of water on clay comparing with others isotherms.